SOSIALISASI TANGGAP BENCANA KEPADA PEMUDA DI DESA POMAHAN KECAMATAN PULUNG KABUPATEN PONOROGO - Imam Utomo; Andhita Risko Faristiana (Universitas Sanata Dharma, 2021)
Natural disasters can occur anywhere and anytime which can cause losses both in terms of material and non-material and can even cause casualties. Pomahan Village, Pulung District, Ponorogo Regency is located in a mountainous area so that the area is prone to disasters both in the form of natural disasters and non-natural disasters such as disasters arising from human activities. Public understanding of disaster mitigation must be improved, especially for the younger generation. It is intended that the risks or impacts arising from the occurrence of disasters can be reduced and the public knows about the first treatment in the event of a disaster. This service activity aims to increase the knowledge and abilities of the youth community in Pomahan village in disaster mitigation management. The implementation of service activities is carried out by holding socialization, discussion and question and answer. The implementation of this socialization activity was carried out to the youth community in Pomahan village. The socialization activity was carried out on Thursday 15 July 2021 which was carried out face-to-face via the Zoom application. The activity was attended by 10 participants from the youth community in Pomahan village. From these socialization activities, youth are expected to be able to apply the knowledge gained during socialization activities in the event of a disaster so that the impact can be reduced. The result of this community service activity is increasing knowledge from the youth community in Pomahan village about disaster mitigation management and first handling when a disaster occurs.